PERLINDUNGAN HUKUM TERHADAP PEKERJA KONTRAK WAKTU TERTENTU MENURUT UNDANG-UNDANG REPUBLIK INDONESIA NOMOR 13 TAHUN 2003 (Studi Kasus Pt. Bhanda Ghara Reksa (Persero) Cabang Semarang) - SANTI, MAYA RATNA (Dinamika Hukum, 2016)
The purpose of this study is to assess the implementation of legal protection and remedies against contract workers time to acquire its rights under Republic Act No.13 of 2003 on Labour in PT. Bhanda Ghara Reksa (Persero) Semarang branch as well as reviewing the role and function of Manpower Semarang in monitoring and providing protection against certain time contract workers at PT. Bhanda Ghara Reksa (Persero) Semarang branch. The research background is the amount of time that a contract worker should be dismissed or appointed as permanent employees, which in practice it is extended annually without certainty, whether the particular time contract workers will be disconnected after the contract period or appointed as a permanent employee. This is certainly contrary to the provisions of Article 59 of Republic Act No.13 of 2003 on Labor, if left unchecked these problems continue it will be a violation of law and human rights violations.The research method is empirical sociological research, which approaches the problem by conducting field research at PT. Bhanda Ghara Reksa (Persero) Semarang branch of legal protection against certain time contract workers under Article 59 of Law No.13 of 2003 on Manpower. The approach used is a single case study (single case study), which is using the case to get more accurate results. Results of this research is the implementation of the legal protection for contract workers a certain time to obtain the rights are not in accordance with the provisions of Law No.13 of 2003 is about workers' rights, which include: Article 6, Article 86, Article 88 paragraph (1) and Article 99 paragraph (1), but it also violates the specified time employment agreement, which include: Article 59 paragraph (1), (2), (4), (5), (6) and (7). Legal remedy certain time contract workers to obtain its rights under Republic Act No.13 of 2003 on Labour in PT. Bhanda Ghara Reksa (Persero) Semarang branch, namely action by reporting to the Trade Unions in the PT. Bhanda Ghara Reksa (Persero) Semarang branch, although the effort is not a maximum or unsatisfactory. Keywords: Worker Protection Law by Law No. 13 of 2003.